Analisis Faktor-Faktor yang Mempengaruhi Konsumsi di Kabupaten Nagan Raya - Dian Ariani (Syiah Kuala University, 2014)
This study aims at analysing what factors determine consumption pattern in Nagan Raya. Secondary data used in the study were collected from Nagan Raya BPS office. A simple regression model was developed to test whether gross domestic regional products as a proxy of regional income has a positive impact on the consumption level. The results the study revealed that autonomous consumption level in Nagan Raya is about IDR 557,35 million meaning that consumption level will increase by IDR 557,35 millions while income level remains constant. In addition, marginal propensity to consume in Nagan Raya is as much as 0.86. This indicates that one percent increase in income will increase consumption level by 0.86 percent. Based on t-test result, income was tatistically significant to explain variation in consumption.